Reduction of Offensive Odor from Natural Rubber Using Zinc-Modified Bentonite - Bryan B. Pajarito; Kayla C. Castañeda; Sofia Denise M. Jeresano; Dominique Ann N. Repoquit (Advances in Materials Science and Engineering)
Natural bentonite was modified with zinc ions and was used as a filler to reduce the offensive odor from raw natural rubber (NR). Characterization of filler shows the limited exchange of inherent calcium ions and the preferred adsorption of zinc ions on the surface of natural bentonite during modification. The modification process was also accompanied by bassanite formation due to sulfate ions brought by the zinc salt. Zinc-modified bentonite demonstrates an antimicrobial effect against microorganisms that are known to degrade or produce offensive odor from raw NR. Due to its antimicrobial and adsorption properties, zinc-modified bentonite significantly reduces the offensive odor from raw NR at loadings of 2.5–7.5 phr as shown by the olfactometry test. In terms of vulcanization characteristics, the loading of zinc-modified bentonite at 7.5 phr caused a slight decrease in elastic torque and increase in scorch and curing times of NR. The hardness and tensile properties of vulcanized NR are maintained after compounding with zinc-modified bentonite at 7.5 phr.